Phenotypic and functional characterization of Bst+/− mouse retina - Hamidreza Riazifar; Guoli Sun; Xinjian Wang; Alan Rupp; Shruti Vemaraju; Fred N. Ross-Cisneros; Richard A. Lang; Alfredo A. Sadun; Samer Hattar; Min-Xin Guan; Taosheng Huang (The Company of Biologists, 2015)
The belly spot and tail (Bst+/−) mouse phenotype is caused by mutations of the ribosomal protein L24 (Rpl24). Among various phenotypes in Bst+/− mice, the most interesting are its retinal abnormalities, consisting of delayed closure of choroid fissures, decreased ganglion cells and subretinal vascularization. We further characterized the Bst+/− mouse and investigated the underlying molecular mechanisms to assess the feasibility of using this strain as a model for stem cell therapy of retinal degenerative diseases due to retinal ganglion cell (RGC) loss. We found that, although RGCs are significantly reduced in retinal ganglion cell layer in Bst+/− mouse, melanopsin+ RGCs, also called ipRGCs, appear to be unchanged. Pupillary light reflex was completely absent in Bst+/− mice but they had a normal circadian rhythm. In order to examine the pathological abnormalities in Bst+/− mice, we performed electron microscopy in RGC and found that mitochondria morphology was deformed, having irregular borders and lacking cristae. The complex activities of the mitochondrial electron transport chain were significantly decreased. Finally, for subretinal vascularization, we also found that angiogenesis is delayed in Bst+/− associated with delayed hyaloid regression. Characterization of Bst+/− retina suggests that the Bst+/− mouse strain could be a useful murine model. It might be used to explore further the pathogenesis and strategy of treatment of retinal degenerative diseases by employing stem cell technology.